Legal Standing and Organization's Right to Sue in Cases of Onrechtmatige Overheidsdaad (Unlawful Government Acts) After the Implementation of Law No. 30 of 2014 - Andriana, Desmilia Eka; Fadli, Moh.; Negara, Tunggul Anshari Setia; Permadi, Iwan (Universitas Islam Negeri Raden Fatah Palembang, 2023)
The government as a legal subject that has the authority to carry out legal acts can actually be tested whether there is no authority approved by the State Administrative Court. This trial can of course be triggered by demands from certain parties who feel disadvantaged by the Government's actions. This research will examine the legal position and right to sue an organization in the Onrechtmatige Overheidsdaad Dispute. This research is normative juridical legal research. This research analyzes the legal position and right to sue the community regarding the defense of the Onrechtmatige Overheidsdaad. The research results concluded three things; First, organizations have sufficient requirements to file a lawsuit because their right to sue is regulated in Law Number 32 of 2009 concerning Environmental Protection and Management (UU 32/2009), and other regulations. Second, UUAP No. 30 of 2016 also regulates the authority to decide whether or not there are elements of authority exercised by Government Officials. This means that Law Number 30 of 2014 provides space for the public to file a lawsuit if there is a rejection of a permit permitted by the government. Third, there is a need to add the word 'organization' and add 'organizational requirements for filing a lawsuit' in UUAP No. 30 of 2014 explicitly.